Un-settling Middle Eastern Refugees: Regimes of Exclusion and Inclusion in the Middle East, Europe, and North America (Volume 40) - Inhorn, Marcia C; Volk, Lucia (Forced migration, 2021)
Since the Iraq war, the Middle East has been in continuous upheaval, resulting in the displacement of millions of people. Arriving from Afghanistan, Iraq, Palestine, and Syria in other parts of the world, the refugees show remarkable resilience and creativity amidst profound adversity. Through careful ethnography, this book vividly illustrates how refugees navigate regimes of exclusion, including cumbersome bureaucracies, financial insecurities, medical challenges, vilifying stereotypes, and threats of violence. The collection bears witness to their struggles, while also highlighting their aspirations for safety, settlement, and social inclusion in their host societies and new homes.